A reconstruction scheme for f(T) gravity: Variable generalized Chaplygin dark energy gas form. Issue 1 (21st January 2021) - Chattopadhyay, Surajit; Chakraborty, Gargee
Abstract : The present study reports a reconstruction scheme for f ( T ) gravity under the assumption that the density due to the torsion T evolves like the variable‐generalized Chaplygin gas (VGCG), a phenomenological candidate of dark energy. This reconstruction has been demonstrated in viscous as well as non‐viscous cases. The state‐finder trajectory r − s has been found to attain the ΛCDM fixed point under this reconstruction scenario. The reconstructed equation of state parameter (EoS) has been studied for their phantom/quintom behavior. The effect of bulk viscous pressure has been found to become prominent in the late stage. The generalized second law (GSL) of thermodynamics has been studied for Bekeinstein ‐ Hawking entropy area relation in both non‐viscous and viscous cases. The GSL is found to be valid in both cases.